Blockade of the Sigma-1 Receptor Relieves Cognitive and Emotional Impairments Associated to Chronic Osteoarthritis Pain - Carcolé, Mireia; Zamanillo, Daniel; Merlos, Manuel; Fernández-Pastor, Begoña; Cabañero, David; Maldonado, Rafael (Frontiers in Pharmacology, 2019)
Osteoarthritis is the most common musculoskeletal disease worldwide, often characterized by degradation of the articular cartilage, chronic joint pain and disability. Cognitive dysfunction, anxiety and depression are common comorbidities that impact the quality of life of these patients. In this study, we evaluated the involvement of sigma-1 receptor (σ1R) on the nociceptive, cognitive and emotional alterations associated with chronic osteoarthritis pain. Monosodium iodoacetate (MIA) was injected into the knee of Swiss-albino CD1 mice to induce osteoarthritis pain, which then received a repeated treatment with the σ1R antagonist E-52862 or its vehicle. Nociceptive responses and motor performance were assessed with the von Frey and the Catwalk gait tests. Cognitive alterations were evaluated using the novel object recognition task, anxiety-like behaviour with the elevated plus maze and the zero-maze tests, whereas depressive-like responses were determined using the forced swimming test. We also studied the local effect of the σ1R antagonist on cartilage degradation, and its central effects on microglial reactivity in the medial prefrontal cortex. MIA induced mechanical allodynia and gait abnormalities that were prevented by the chronic treatment with the σ1R antagonist. E-52862 also reduced the memory impairment and the depressive-like behaviour associated to osteoarthritis pain. Interestingly, the effect of E-52862 on depressive-like behaviour was not accompanied by a modification of anxiety-like behaviour. The pain-relieving effects of the σ1R antagonist were not due to a local effect on the articular cartilage, since E-52862 treatment did not modify the histological alterations of the knee joints. However, E-52862 induced central effects revealed by a reduction of the cortical microgliosis observed in mice with osteoarthritis pain. These findings show that σ1R antagonism inhibits mechanical hypersensitivity, cognitive deficits and depressive-like states associated with osteoarthritis pain in mice. These effects are associated with central modulation of glial activity but are unrelated to changes in cartilage degradation. Therefore, targeting the σ1R with E-52862 represents a promising pharmacological approach with effects on multiple aspects of chronic osteoarthritis pain that may go beyond the strict inhibition of nociception.